Strengthening Public Administration Concepts in Administrative Implementation at the Pulau Pekan Village Office, Bungo Regency, Jambi, Indonesia - Bakar, Abu; Syahwami; Marlina, Eva; Hamirul; Mardansyah (Indonesian Community Empowerment Journal, 2023)
Public administration is a series of activities carried out by the government in order to provide services to the community. The successful implementation of public administration is greatly influenced by the correct understanding and application of public administration concepts. This research aims to increase understanding and application of public administration concepts in the implementation of administration at the Pulau Pekan Village Office, Bungo Regency, Jambi, Indonesia. The method for implementing community service used in this activity is a workshop on strengthening the concept of public administration in the implementation of government administration in Pulau Pekan Village, Bungo Regency, Jambi. The results of the activity show that the understanding and application of public administration concepts at the Pulau Pekan Village Office still needs to be improved. This can be seen from the existence of several problems in administrative implementation, such as a lack of understanding of the principles of public administration, a lack of implementation of standard administrative procedures, and a lack of coordination between work units. To overcome this problem, it is necessary to strengthen the concept of public administration at the Pulau Pekan Village Office. This strengthening can be carried out through various activities, such as training, mentoring, and improving facilities and infrastructure.